Motivation to employment by oriental combat sports in system of physical training of high schools - Литвиненко [Litvinenko A.], Олександр Миколайович (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Are considered questions of use of means and methods of oriental combat sports for optimization of physical training of students of high schools. The motivation of students to employment by physical training and efficiency of the differentiated approach to formation of groups of initial sports preparation is investigated. Researches rotined that the increase of level of physical preparedness of students caused changes in motivation to employments by east single combats; prevailing is become by reason of achievement of sporting results. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->